Le contrôle de la légalité : une compétence exclusive des cours supérieures - Duplé, Nicole (Les Cahiers de droit, 1978)
In the Farrah case, the Supreme Court of Canada declared unconstitutional a provision in Quebec Transport Act on the grounds that, when read with privative clauses also contained in the Act, it purported to vest in the Transport Tribunal jurisdiction analogous to the Superior Court's jurisdiction to review proceedings before inferior tribunals in the province. Five members of the Court held that, while a provincial Legislature may, by enacting privative clauses, preclude review by the Superior Court of decisions made by a tribunal within its jurisdiction, it cannot transfer the power to review such matters to a provincially-appointed tribunal, since review powers can only be exercised by courts listed in s. 96 of the BNA Act.